Analysis of the particles-induced turbulence in confined gas-solid fluidized beds by PR-DNS. (August 2021) - Wang, Dong; Jin, Tai; Luo, Kun; Tan, Junhua; Fan, Jianren
Highlights: Particle-resolved simulations of bubbling fluidized beds are performed by using the immersed boundary method. Mean and second order statistics of velocity are derived from the particle-resolved simulations. The streamwise Reynolds-averaged momentum equation and the turbulent kinetic energy equation are evaluated at different heights of the bubbling beds. The kinetic energy transfer between particles and fluid is analysed from the mean and fluctuation perspectives. Abstract: Particles-induced turbulence in fluidized beds is vital in dense particulate flow and still lacks detailed investigation. In this study, a multi-direct forcing immersed boundary method coupled with a soft-sphere model is employed in simulations of shallow and deep bubbling beds of movable spheres. Five different particle-resolved direct numerical simulations are performed by varying the inlet gas velocity, the bed extent, and the number of particles. The particles-induced turbulence under the wall effect in the bubbling beds is analysed, including the mean and second-order statistics of velocity, momentum balance, turbulent kinetic energy balance, and kinetic energy transfer between particles and fluid. It is found that the turbulence intensity is greater at the location where the bubble bursts. An analysis of the Reynolds-averaged (RA) momentum equation shows that the mean streamwise feedback force term and the mean pressure gradient term are the most critical terms in particles' presence. An analysis of the turbulent kinetic energy (TKE) equation shows that the pressure dilatation term is the source term generating the TKE, while the interphase exchange term is the dissipation term reducing the TKE in particles' presence. A detailed analysis of the kinetic energy transfer between particles and fluid is finally conducted.